Criminal charge models for legal entities: reality or fiction? - Muñoa Vidal, Tania (2025)
The maxim of Societas delinquere non potest has mutated into the non-maxim but accepted Societas delinquere potest, whereby the legal person, in addition to being a passive subject of criminal law, becomes an active subject, but under the question of not having the capacity for criminal action and guilt; in this context, the present investigation was proposed to probe the current theoretical doctrinal state on which the responsibility of the legal person is based, with the general objective of analyzing the models of criminal imputation of the criminal responsibility of the business entity. Under a qualitative approach and using legal research methods of theoretical, historical and exegetical analysis, the results show the existence of models that run between the imputation of self-responsibility, of hetero-responsibility, mixed model, and the model of organization and management, where criminal responsibility is conditioned to the organizational defects of the company. The study warns about the lack of imputation schemes based on criminal dogma, which allowed us to conclude about the legal paradox that, even though there is a legislative recognition of criminal liability of the legal entity, the models do not show a coherent criminal theory and doctrine of corporate imputation.